2012
DOI: 10.1002/pbc.24285
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance following head, neck, and chest radiotherapy: Thyroid ultrasound monitoring for secondary thyroid malignancy

Abstract: Children who receive head, neck, or chest radiotherapy for various primary malignancies have increased risk for secondary thyroid malignancy. Thyroid nodules are difficult to identify by physical examination and/or laboratory tests. Thyroid ultrasound can detect non-palpable nodules without adverse side effects. We performed a retrospective chart review of 36 patients who received radiotherapy and underwent thyroid ultrasound. Forty-seven percent (n = 17) had ≥1 nodule(s) detected. Seven patients underwent thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Those who were found to have thyroid nodules were older than those who did not, supporting the well-known relationship between time of exposure and the development of nodules. This latency period between radiation exposure and the development of thyroid cancer has been described from the follow-up studies of children exposed to external radiation for the treatment of thymic enlargement [25], childhood malignancies [22,26], and the effects of the Chernobyl nuclear accident [27,28]. The most significant risk for these reported populations is seen between 5 and 9 years from exposure [21].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Those who were found to have thyroid nodules were older than those who did not, supporting the well-known relationship between time of exposure and the development of nodules. This latency period between radiation exposure and the development of thyroid cancer has been described from the follow-up studies of children exposed to external radiation for the treatment of thymic enlargement [25], childhood malignancies [22,26], and the effects of the Chernobyl nuclear accident [27,28]. The most significant risk for these reported populations is seen between 5 and 9 years from exposure [21].…”
Section: Discussionmentioning
confidence: 97%
“…The damage invoked to the thyroid gland by head, neck, or chest radiotherapy for the treatment of various primary malignancies has recently been described [22,23]. Children treated for hydrocephalus may also be subjected to significant cumulative radiation dosages by repeated CT scans, exposing the developing thyroid gland to damaging effects.…”
Section: Discussionmentioning
confidence: 99%
“…Members of minority racial/ethnic groups tend to be more vulnerable to PTSS than members of majority groups, even after controlling for sociodemographic, clinical and social support factors (Adams & Boscarino, 2005; Alim, Charney, & Mellman, 2006; Kessler et al, 1995; Meeske et al, 2013; Stephens et al, 2010). One explanation for this disparity is that racial/ethnic minority groups tend to experience more traumatic events than majority groups, and past trauma exposure has been found to be a strong predictor of future PTSD/PTSS (Alim, Charney, & Mellman, 2006; Hogue & Bremmer, 2005; Schulz et al, 2000).…”
mentioning
confidence: 93%
“…Of the few studies conducted with minority groups, the findings for racial/ethnic disparities have been inconsistent (Meeske et al, 2013; Stoppelbein & Greening, 2007). Meeske et al (2013), for example, found higher rates of PTSS among Hispanic parents of childhood cancer survivors that were more than 2 years off treatment when compared to non-Hispanic parents of childhood cancer survivors off treatment; whereas Stoppelbein and Greening (2007) did not find racial/ethnic differences among parents of children with cancer versus T1DM. These equivocal findings might in part be due to the fact that many studies did not control for SES.…”
mentioning
confidence: 99%
“…Besides increasing the risk for differentiated thyroid carcinoma, radiotherapy involving the thyroid gland is also known to promote the occurrence of benign thyroid nodules in childhood cancer survivors (Table 11). Clinically, it may be difficult to distinguish malignant from benign thyroid nodules (Healy et al 1996, Crom et al 1997, Somerville et al 2002, Acharya et al 2003, Haddy et al 2012, Vivanco et al 2012, Kelly et al 2013, Caglar et al 2014, Agrawal et al 2016, Brignardello et al 2016. Studies investigating radiation-related thyroid carcinoma risk after childhood cancer treatment have predominantly assessed older radiotherapeutic modalities.…”
Section: :6mentioning
confidence: 99%